Shooting Kabul - Senzai N. H. (New York : Scholastic, 2010)
Escaping from Taliban-controlled Afghanistan in the summer of 2001, eleven-year-old Fadi and his family immigrate to the San Francisco Bay Area, where Fadi schemes to return to the Pakistani refugee camp where his little sister was accidentally left behind.
M
800
Keywords: War; Soldier